The Relationship between Emotional Intelligence and Suicide Ideation in Students Who Are Working on Thesis - Zidny, Muhammad Irfan; Nurmina (Causalita, 2025)
Suicide ideation is an early stage that can develop into suicide if not handled properly. Students who are in the stage of preparing a thesis often face pressure from academic, emotional, and also their social environment, so they are at risk of experiencing mental health problems. In this case, emotional intelligence plays an important role as a protective mechanism, because it involves individual skills in recognizing, understanding, and regulating emotions effectively. This study aims to determine the relationship between suicide ideation and emotional intelligence in students who are working on a thesis at Padang State University. This research uses correlational methodology with a quantitative approach. The population in this study included students in semester seven to fourteen, and a total of 272 respondents were obtained using purposive sampling technique. In the process of collecting data, the research was carried out by utilizing two types of measurement scales, namely the emotional intelligence scale based on the theory of Salovey and Mayer (1990) developed by Maryam & Rusli (2021), and the Beck Suicide Ideation (BSS) scale from Beck (1997) adapted by Kesuma et al. (2021). The findings of this study indicate that there is a significant negative relationship between suicide ideation and emotional intelligence in other words, the higher a person's emotional intelligence, the less likely they are to have suicide ideation.